Hubungan Karakteristik Sosial Ekonomi Dengan Pendapatan Petani Pengguna Teknologi Rice Transplanter di Kecamatan Indrapuri Aceh Besar - Mardhiah, Ainal; Puspita, Diah Eka; Hayati, Rahmah; Mulyadi, Mulyadi; Fuadi, Zahrul (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The use of rice transplanter technology, which requires less labor in the rice planting process, is increasingly being adopted by farmers. However, despite the implementation of rice transplanter technology, some farmers still prefer to maintain traditional methods due to their perceived effectiveness in ensuring the precision of seed planting. This study aims to analyze the income of farmers who use rice transplanter technology and explore the relationship between the farmers' socio-economic characteristics and their income. The results show that the average income of farmers using Rice Transplanters in Indrapuri, Aceh Besar, reaches Rp 16,551,529 per planting season, with an average income of Rp 49,364,210.5 per hectare. Socio-economic characteristics of farmers, such as age, education level, and land area, have a significant positive relationship with income, while the number of dependents and farming experience show a negative relationship with the income of rice transplanter users. In conclusion, the application of rice transplanter technology can increase farmers' income, especially when supported by favorable socio-economic characteristics, such as education level and the area of land managed.